2006
DOI: 10.1016/j.yfrne.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and brain-derived neurotrophic factor (BDNF) in hippocampus: Complexity of steroid hormone-growth factor interactions in the adult CNS

Abstract: In the CNS, there are widespread and diverse interactions between growth factors and estrogen. Here we examine the interactions of estrogen and brain-derived neurotrophic factor (BDNF), two molecules that have historically been studied separately, despite the fact that they seem to share common targets, effects, and mechanisms of action. The demonstration of an estrogen-sensitive response element on the BDNF gene provided an impetus to explore a direct relationship between estrogen and BDNF, and predicted that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
210
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(214 citation statements)
references
References 244 publications
4
210
0
Order By: Relevance
“…Exogenous estradiol administration to ovariectomized rats increases BDNF mRNA and protein expression in the hippocampus (Gibbs, 1998, Jezierski and Sohrabji, 2001, Scharfman et al, 2003, Zhou et al, 2005. Activation of the BDNF receptor TrkB in the hippocampal formation leads to LIMK and Akt phosphorylation, dendritic spine regulation, and enhancement of long-term potentiation, similar to the effects of estradiol (Chao, 2003, Scharfman and Maclusky, 2005, Scharfman and Maclusky, 2006a, Spencer et al, 2007.…”
mentioning
confidence: 82%
“…Exogenous estradiol administration to ovariectomized rats increases BDNF mRNA and protein expression in the hippocampus (Gibbs, 1998, Jezierski and Sohrabji, 2001, Scharfman et al, 2003, Zhou et al, 2005. Activation of the BDNF receptor TrkB in the hippocampal formation leads to LIMK and Akt phosphorylation, dendritic spine regulation, and enhancement of long-term potentiation, similar to the effects of estradiol (Chao, 2003, Scharfman and Maclusky, 2005, Scharfman and Maclusky, 2006a, Spencer et al, 2007.…”
mentioning
confidence: 82%
“…Therefore, the physiopathology of climacteric signs including depression, hot flashes etc., may correlate with the wide spectrum of sex hormones actions on neurons functions both directly through hormone receptor relations and indirectly via alterations in neurotransmitter concentration and neurotrophin activity (51). Some reports suggesting the involvement of BDNF in regulating estrogen actions showed that it could modulate the expression of BDNF via the estrogen response element on the BDNF gene (18,52). In recent years, the importance of non-hormonal alternatives for the decreasing the climacteric symptoms has enhanced, i.e.…”
Section: Brain Derived Neurotrophic Factor or Bdnfmentioning
confidence: 99%
“…Cholinergic input from the septum seems to modulate spatial memory (Smith and Pang, 2005); these same neurons transport BDNF protein from hippocampus to septum (Sobreviela et al, 1996). Furthermore, BDNF protein levels are naturally elevated during proestrus and estrus (Scharfman et al, 2003), and changes in BDNF mRNA and protein have been reported in ovariectomized rats after acute (Gibbs, 1999) and chronic (Zhou et al, 2005) estradiol treatment (for review see Scharfman and MacLusky, 2006). If multiparity exerts long-term changes on hippocampal (or septal) BDNF protein, it is possible that BDNF may underlie any positive effects of parity on spatial memory.…”
mentioning
confidence: 99%